Isсhemic change in bronchus stump after lung cancer resection - S. A. Plaksin; L. I. Farshatova; A. L. Lisichkin (Вестник хирургии имени И.И. Грекова, 2020)
The OBJECTIVE of the study was to assess the changes in blood supply of the bronchus stump following lung resection with lymph node dissection.METHODS AND MATERIALS. Bronchial microcirculation was studied in 8 patients during pneumonectomy of the wall of the main bronchus using laser Doppler flowmetry method. In this paper, we present our observations of postoperative necrotic ischemic bronchitis after lobectomy with associated formation of bronchopleural fistula of the main bronchus and the failure of the stump of the lobular bronchus.RESULTS. Mobilization of the bronchus decreased microcirculation rate to (3.3±0.3) conventional units (c. u.), or to 74.5 %; lymphatic dissection further reduced microcirculation rate to (2.6±0.2) c. u., or to 60.2 %. An additional twisted suture was found to worsen ischemia. The normalized value of the amplitude decreased during the second minute of the dissection of the bronchus, indicating hypoxia. A 61-year-old patient with diabetes showed damage to the wall of the main bronchus 0.6 cm in size 7 days after undergoing the right lower lobectomy with lymphatic dissection. On the 19th day after the same procedure, the same patient developed an insolvency of the stump of the lower lobe bronchus, which was classified as a manifestation of ischemia. Postoperative ischemic bronchitis can occur in a true ischemic or an ulcerative necrotic form, and it can be diagnosed using a macroscopic picture in the context of fibrobronchoscopy. It occurs in (2.5–3.2) % of patients who underwent lung resections for cancer with lymphatic dissection.CONCLUSION. Ischemia of the bronchial wall during its mobilization plays a significant role in the etiology of bronchopleural fistula. Lymphatic dissection worsens microcirculation of the bronchial wall. Ischemic necrotic bronchitis can lead to formation of the bronchopleural fistula outside of the stump. High-risk patients require additional coverage of the bronchus stump with muscle or fat tissue.